Applying theory to generalist social work practice : a case study approach - Langer, Carol L.; Lietz, Cynthia A. (John Wiley & Sons, Inc., 2015)
"The authors begin with an overview how theories are used in social work practice. The book then covers twelve evidence-based theories that are most commonly used by social workers with an undergraduate degree only: ecological & systems theory, stengths perspective, task-centered appraoch, conflict theory, humanistic & client centered, cognitive and behavioral theories, empowerment theory, constructivism, narrative theory, solution focused brief therapy, crisis theory, and critical and feminist theory"--